Investigating the Correlations among Witt's and ANB Cephalometric Indices and the Upper Pharyngeal Airway Width in Individuals with Class III Malocclusion: A Cross-Sectional Study - Mehrnaz Alirezaei; Aliakbar Naghavialhosseini; Mina Pakkhesal; Mehrnoosh Alirezaei; Nasser Behnampour (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Background and aim: Craniofacial and airway structures are visible in lateral cephalometric radiography. Witt's appraisal and ANB angle are cephalometric analysis indicators, which play essential roles in diagnosing class III malocclusion. In the current study, the correlations among Witt's and ANB cephalometric indices and the upper pharyngeal airway width has been investigated in individuals with class III malocclusion. Materials and methods: This cross-sectional study was performed on 110 lateral cephalometric radiographs of 11-14-year-old patients during 2017-2020. The upper pharyngeal airway width was determined by p index (the shortest distance between the soft palate and the posterior pharyngeal wall) and the t index (the shortest distance between the tongue base and the posterior pharyngeal wall) through lateral cephalometric radiography. The data were designated by central tendency indicators and measures of dispersion. The Shapiro-Wilk test evaluated data normality. Also, the Spearman correlation coefficient was used to determine the correlation rate. Results: Investigating the correlations among indicators showed a direct but dramatically low relationship in ANB and p values and Witt's and p values. However, these relationships were not statistically significant. There was also an inverse linear relationship between ANB and t values and Witt's and t values. Nevertheless, the results showed the mean values of p, t, ANB, and Witt's indices were higher in females than males, yet, the differences in p and ANB values were not statistically significant. Conclusion: Results showed the correlation coefficients among the upper pharyngeal airway width, and ANB and Witt's analyses were not significant. These results can reinforce the probability of class III malocclusion inheritance.